Adding Insult to Injury: The Accumulation of Stigmatizing Language on Individuals With Lived Experience of Self-Injury - Hasking, Penelope; Staniland, Lexy; Boyes, Mark; Lewis, S.P. (LIPPINCOTT WILLIAMS & WILKINS, 2022)
Language is a powerful form of communication that not only conveys ideas and knowledge but also can assign meaning and value to the world around us. As such, language has the power to shape our attitudes toward individuals, behaviors, and ideas, by labeling them (indirectly or not) as "good"or "bad."In this way, language can be used to propagate stigma and other unhelpful attitudes toward individuals who already experience stigma. One behavior that may be particularly prone to the impact of unhelpful language is nonsuicidal self-injury (NSSI). In this article, we draw on Staniland's NSSI stigma framework to demonstrate how an individual with lived experience of NSSI may be exposed to stigmatizing messaging through 30 different channels, and propose that the accumulation of these messages may be particularly damaging. We conclude by offering practical tips for clinicians and researchers wishing to empathically work with individuals who self-injure.